STRATEGI DIGITAL BUSINESS DALAM MENGEMBANGKAN USAHA BAGI WIRAUSAHAWAN MILLENIAL - Gita Nurul Fitri Damanik; Anisa Aulia; Purnama Ramadani Silalahi (INTERNATIONAL, Journal of Sharia Business Management, 2022)
Marketing through digitization media is very influential on young entrepreneurs by utilizing existing social media. In the use of social media such as Instagram, Facebook, WhatsApp, websites, platforms that can be used as brand enhancement, public interest in the products to be marketed, cooperation between entrepreneurs and loyalty. Currently the use of digital technology as an alternative in doing business. The purpose of this research is to find out the use of digital business strategies in developing businesses for millennial entrepreneurs. The method used in this study is a qualitative method using secondary data sourced from books, journals, other supporting scientific articles. This research is a literature study. Based on the results of the study, it was concluded that digital business strategies have an effect on developing businesses that are being run by millennial entrepreneurs. Digital transformation is currently in the spotlight and requires in-depth consideration when responding to developments in information technology. In the millennial era, innovation is needed due to increasingly fierce competition in the business world. Using e-commerce and startup as a business innovation that is able to compete in the globalization era.